1990
DOI: 10.1128/jcm.28.11.2491-2495.1990
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-linked immunoassay for detection of Cryptosporidium antigens in fecal specimens

Abstract: Cryptosporidium sp. is a ubiquitous 4- to 6-micron protozoan parasite infecting the intestinal tract of humans. It causes mild to fulminant diarrhea in patients, especially immunocompromised persons, and it may be hard to detect by microscopic fecal examination. An indirect, double-antibody enzyme-linked immunosorbent assay (ELISA) was developed using specifically produced goat and rabbit antisera to detect Cryptosporidium antigens in human feces. Of 62 frozen stools from patients with cryptosporidiosis, as de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…They attributed decreased sensitivity to repeated freezing and thawing of specimens. (34) The diagnostic performance of the ELISA in the present study revealed moderate sensitivity and specificity. The PPV, which indicates the probability of having cryptosporidiosis among diarrheic children was relatively high (68.7%).…”
Section: Discussionmentioning
confidence: 48%
“…They attributed decreased sensitivity to repeated freezing and thawing of specimens. (34) The diagnostic performance of the ELISA in the present study revealed moderate sensitivity and specificity. The PPV, which indicates the probability of having cryptosporidiosis among diarrheic children was relatively high (68.7%).…”
Section: Discussionmentioning
confidence: 48%
“…Spleens were removed, B-lymphocytes were fused with FOX.NY myeloma cells, and the cells were grown in Dulbecco's modified Eagle's medium (DMEM), as described before (6). Supernatants were tested for anti-Cryptosporidium antibodies by enzyme-linked immunosorbent assay (ELISA) (34,37). Hybridomas producing anti-C. parvum antibody were cloned by limiting dilution and further assessed for reactivity by Western immunoblot analysis (see below).…”
Section: Methodsmentioning
confidence: 99%
“…The sensitivity and specificity of these methods vary, depending on the protocol used. Various screening methods for Cryptosporidium oocysts from, primarily, fresh human faecal samples have been studied (Garcia et al 1987;Ungar 1990;Siddons et al 1992;MacPherson and McQueen 1993;Tee et al 1993;Aarnaes et al 1994;Parisi and Tierno 1995;Garcia and Shimizu 1997;Johnston et al 2003;Magi et al 2006). These studies have produced conflicting results and it is reasonable to deduce that there is currently no available gold standard diagnostic method.…”
Section: Introductionmentioning
confidence: 99%